Abu Dhabi International Petroleum Exhibition and Conference 2014
DOI: 10.2118/172083-ms
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Gas Recovery by CO2 Sequestration versus Re-fracturing Treatment in Unconventional Shale Gas Reservoirs

Abstract: It is proposed that very low permeability formations are possible candidates for CO 2 sequestration. Further, experimental studies have shown that shale formations have huge affinity to adsorb CO 2 , the order of 5 to 1 compared to the methane. Therefore, potential sequestration of CO 2 in shale formations leading to enhanced gas recovery (EGR) will be a promising while challenging target for the oil and gas industry. On the other side, hydraulic re-fracturing treatment of shale gas wells is currently gaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…In some simulation studies, CO 2 huff-n-puff [89,91] for EGR were not effective in shale gas reservoirs. Yu et al [89] found the recovery for huff-n-puff CO 2 injection was lower than the one without CO 2 injection.…”
Section: Field-scale Simulation Studymentioning
confidence: 99%
See 2 more Smart Citations
“…In some simulation studies, CO 2 huff-n-puff [89,91] for EGR were not effective in shale gas reservoirs. Yu et al [89] found the recovery for huff-n-puff CO 2 injection was lower than the one without CO 2 injection.…”
Section: Field-scale Simulation Studymentioning
confidence: 99%
“…They explained that the unfavorable performance for CO 2 huff-n-puff was because of a large amount of CO 2 (96%) flowing back to the surface in the puff stage without carrying out much CH 4 and the CO 2 adsorption effect was negligible. Eshkalak et al [91] numerically compared the efficiency of hydraulic re-fracturing treatment to CO 2 -EGR approaches (flooding and huff-n-puff) to improve gas production in shale with reservoir permeability of 100 nd. The simulation results indicated that for the CO 2 huff-n-puff injection, after the five-year shut-in period, almost all the injected CO 2 (96%) was produced back.…”
Section: Field-scale Simulation Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the value of 60 nm is used as the pore radius in this case. The rest parameters are taken from Aybar et al [8], which are based on the typical fluid and rock properties for an unconventional gas reservoir [23,24]. The target depth for this study is set to be 2500 m with the assumption of hydro-static pressure gradient.…”
Section: The Coupled Effect Of Poro-elastic Compaction and Slip Flowmentioning
confidence: 99%
“…The approach considered competitive transport and adsorption effect in the organic micropores of the shale during CO 2 injection but they only considered Huff 'n' Puff scenario. Examiningboth CO 2 Huff 'n' Puff and CO 2 flooding-, Eshkalak et al (2014) concluded that Huff 'n' Puff process is not a viable option for CO 2 -EGR. Jiang et al (2014) developed a multi-continuum simulator with pressure-dependent permeability for CO 2 -EGR process in fractured shale gas reservoirs.…”
Section: Introductionmentioning
confidence: 99%